PENGARUH LIKUIDITAS, STRUKTUR MODAL DAN AKTIVITAS TERHADAP NILAI PERUSAHAAN - Revata, Richellieu; Almalita, Yuliani (E-Jurnal Akuntansi TSM, 2023)
The purpose of this study was to determine an empirical evidence regarding the effect of profitability, capital structure, managerial ownership, institutional ownership, liquidity, activity, dividend policy, and firm size as independent variable on firm value as dependent variable. The population in this study used non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period, 53 companies passed with a total of 159 data used for this study. The sampling technique used purposive sampling method with determining criteria in determining the population. The results of this study shows that profitability have a negative effect because some investors choose to buy shares of companies that have experienced a decline in profits. The capital structure have a positive effect because a good capital structure shows good business prospects in the future. Liquidity have a negative effect, due to high liquidity focusing the company on meeting short-term obligations rather than distributing shareholder dividends. Firm size have a positive effect on firm value because large firm size will result in greater profits and make it easier for firms to obtain external capital. Meanwhile, managerial ownership, institutional ownership, activity, dividend policy have no effect on firm value.